Sources of diel variation in energetic physiology in an Arctic-breeding, diving seaduck - Steenweg, Rolanda J.; Hennin, Holly L.; Bêty, Joël; Gilchrist, H. Grant; Williams, Tony D.; Crossin, Glenn T.; Love, Oliver P. (General and Comparative Endocrinology, 2015)
Diel variation in baseline glucocorticoid (GC) secretion influences energetics and foraging behaviors. In temperate breeding, diurnal vertebrates, studies have shown that daily patterns of baseline GC secretion are influenced by environmental photoperiod, with baseline GCs peaking prior to sunrise to stimulate waking and foraging behaviors. Measures of physiological energy acquisition are also expected to peak in response to foraging activity, but their relationship to GC levels have not been well studied. In contrast to temperate breeding species, virtually nothing is known about diel GC and energetic metabolite secretion in Arctic breeding species, which experience almost constant photoperiods in spring and summer. Using a ten-year dataset, we examined the daily, 24-h pattern of baseline corticosterone (CORT) and triglyceride (TRIG) secretion in approximately 800 female pre-breeding Arctic-nesting common eiders (Somateria mollissima). We related these traits to environmental photoperiod and to tidal cycle. In contrast to temperate breeding species, we found that that neither time of day nor tidal trend predicted diel variation in CORT or TRIG secretion in Arctic-breeding eiders. Given the narrow window of opportunity for breeding in polar regions, we suggest that eiders must decouple their daily foraging activity from light and tidal cycles if they are to accrue sufficient energy for successful breeding. As CORT is known to influence foraging behavior, the absence of a distinct diel pattern of CORT secretion may therefore be an adaptation to optimize reproductive investment and likelihood for success in some polar-breeding species.